Supply Chain Strategy in Modernization of State Support Instruments for Small Farms in Ukraine - Olga M, Varchenko; Dmytro F, Krysanov; Olena V, Shubravska; Larysa P, Khakhula; Olecya Y, Gavryk; Valentyna A, Byba; Inna V, Honcharuk (International Journal of Supply Chain Management, 2020)
Abstract- Sustainable food value chains can offer important pathways out of poverty for the millions of small farms in developing countries. The need to concentrate state support for the development of small farms is proved in the article. The results of the cluster analysis of small farms show that it is advisable to send state support to the development of farms in which revenues are generated from the sale of crop products, as well as from other crop products - "niche" products and animal husbandry. The necessity to develop regional programs of support for small-scale farms producing â€œnicheâ€ crops, which would provide for compensation of material costs for its production in the amount of 50% of the value of cost standards, is substantiated. The procedure for providing such support was elaborated and the possibilities of financial support were determined according to the principle of co-financing of the united territorial community and state bodies in the ratio of 50:50. The feasibility of state support for beginning farmers on the basis of a grant for the creation of a family livestock farm, the maximum size of which should be: for breeding cattle of meat and dairy areas no more than 60%, pigs and poultry - 50% of regulatory costs is proved. The financial basis for the program for supporting the development of farms for the production of livestock products should be from the funds of the local united territorial communities and the state budget in the ratio of 30:70.